PIEZO1 Is Selectively Expressed in Small Diameter Mouse DRG Neurons Distinct From Neurons Strongly Expressing TRPV1 - Wang, Jigong; La, Jun-Ho; Hamill, Owen P. (Frontiers in Molecular Neuroscience, 2019)
Using a high resolution in situ hybridization technique we have measured PIEZO1, PIEZO2 and TRPV1 transcripts in mouse dorsal root ganglion (DRG) neurons. Consistent with previous studies, PIEZO2 transcripts were highly expressed in most DRG neurons, including the largest diameter neurons implicated in mediating touch and proprioception. In contrast, PIEZO1 transcripts were selectively expressed in smaller diameter DRG neurons, which are implicated in mediating nociception. Moreover, neurons expressing PIEZO1 were distinct from those neurons that strongly expressed TRPV1, one of the channels implicated in heat-nociception. Using an in vivo functional test for the selective expression, we found that Yoda1, a PIEZO1-specific agonist, induced a mechanical hyperalgesia that displayed a significantly prolonged time course compared with that induced by capsaicin, a TRPV1-specific agonist. Taken together, our results indicate that PIEZO1 should be considered a potential candidate for the long sought channel mediating mechano-nociception.